2014
DOI: 10.1542/peds.2014-0442
|View full text |Cite
|
Sign up to set email alerts
|

Missed Opportunities for HPV Vaccination in Adolescent Girls: A Qualitative Study

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Rates of human papillomavirus (HPV) vaccination lag behind other adolescent vaccines. Research indicates that provider recommendation is the key to improving HPV vaccination rates and that most adolescents who are unvaccinated received other vaccines, indicating missed opportunities for HPV vaccination. WHAT THIS STUDY ADDS:This study explores in-depth the content of provider-patient conversations that either create or prevent opportunities for HPV vaccination. Effective and ineff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
151
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(155 citation statements)
references
References 19 publications
4
151
0
Order By: Relevance
“…29,35,36 Perceptions of parental hesitancy toward HPV vaccination were also negatively associated with communication; providers who perceived parents as unsupportive less often recommended or intended to recommend HPV vaccine. 12,29,33,35,[37][38][39] Conversely, providers who perceived professional organizations as influential more often recommended or intended to recommend the vaccine. [23][24][25]37,[40][41][42][43] Other frequently studied perceptions included those related to providers' confidence in HPV vaccine and their own abilities to discuss it.…”
Section: Preferences In Communication Source By Provider Typementioning
confidence: 99%
See 3 more Smart Citations
“…29,35,36 Perceptions of parental hesitancy toward HPV vaccination were also negatively associated with communication; providers who perceived parents as unsupportive less often recommended or intended to recommend HPV vaccine. 12,29,33,35,[37][38][39] Conversely, providers who perceived professional organizations as influential more often recommended or intended to recommend the vaccine. [23][24][25]37,[40][41][42][43] Other frequently studied perceptions included those related to providers' confidence in HPV vaccine and their own abilities to discuss it.…”
Section: Preferences In Communication Source By Provider Typementioning
confidence: 99%
“…29,32,37,44,45 In contrast, no studies found a correlation between providers' perceptions of HPV vaccine safety and their recommendation behaviors, perhaps because concerns about safety were relatively uncommon. 27,32,36,38,44,45 In terms of providers' perceptions of themselves, self-efficacy to communicate about HPV vaccine was associated with recommending and intending to recommend the vaccine. 12,26,46 Interestingly, providers who viewed themselves as "early adopters" were also more likely to recommend HPV vaccine.…”
Section: Preferences In Communication Source By Provider Typementioning
confidence: 99%
See 2 more Smart Citations
“…These behaviors constitute important intermediary steps between parents' vaccination intentions and adolescents' vaccination status. Although the qualitative literature suggests that HPV vaccine refusal and delay are common, 7,8 only one study has estimated their national prevalence. 9 In 2010, a special addendum to the National Immunization Survey (NIS)-Teen assessed these behaviors, finding that 20% of parents of adolescent girls reported HPV vaccine refusal while an additional 11% reported delay.…”
mentioning
confidence: 99%